The archaeology of Dian : trends and tradition - Allard, Francis
The Dian culture of eastern Yunnan in southwest China is known particularly for its fine material culture. Much new work has been done to explore the militaristic Dian, and this paper provides an up-to-date discussion of its importance and its archaeology.